THE ROLE OF JUDICIAL REVIEW IN THE INDONESIAN LEGAL SYSTEM: A LITERATURE REVIEW ON CONSTITUTIONAL PROTECTION AND LEGAL ACCOUNTABILITY - Danang Rahmat Surono; Gunawan Widjaja (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This study discusses the role of judicial review in the Indonesian legal system using a literature review approach, focusing on two main aspects, namely constitutional protection and legal accountability. Judicial review conducted by the Constitutional Court has a strategic function in maintaining constitutional supremacy through a mechanism for reviewing laws against the 1945 Constitution, thereby ensuring that applicable regulations do not violate the constitutional rights of citizens. In addition to acting as a guardian of the constitution, judicial review also acts as an instrument of accountability that demands openness and accountability from the legislative and executive branches in the formulation and implementation of laws. The literature review method was used to explore literature, Constitutional Court decisions, and related legal documents, thereby obtaining a comprehensive understanding of the contribution of judicial review in the Indonesian legal system. The results of the study show that judicial review is not only important in protecting rights and the rule of law, but also in strengthening transparent and accountable governance. Strengthening access and balancing the authority of state institutions are key to the development of effective judicial review in the future.